Efek Perendaman Serat Sabut Kelapa dalam Larutan Alkali Terhadap Daya Serap Serat Sabut Kelapa pada Matriks Poliester - Habe, Muhammad Arsyad (Politeknik Negeri Ujung Pandang, 2016)
The aim of this study is to determine the effects of soaking the coconut fiber in alkaline fluid on absorption capability of the coconut fiber on polyester matrix. The coconut fiber is soaked in natrium hidroksida (NaOH) fluid with concentration of 20% for duration range of 1, 3,5, 7, 9 and 11 hours, then dried in room temperature then matrix polyester is given on several parts of the coconut fiber. After dried, wet ability angle is measured using digital microscope to investigate the absorption capability of the coconut fiber on polyester matrix. Every single variable will be examined for three times. Obtained data will be analyzed statistically using discriminative method and will be demonstrated in table form. Based on experiment, soaking of coconut fiber in 20% natrium hidroksida (NaOH) fluid affects on absorption capability of the coconut fiber on polyester matrix. After soaked, wet ability angle is decreased compared to without soaked. The smallest wet ability angle of 15,327o is obtained for 5 hours soak duration.